Causal relationship of stock performance and macroeconomic variables: Empirical evidences from Brazil, Russia, India and China (BRIC) - Celis, Evelita Estela (Archives of Business Research, 2017)
The rise of BRIC (Brazil, Russia, India and China) in the global investment market is still too mysterious to investors. This paper attempts to investigate the causal relationship among quarterly returns of BRIC’s stock market indices using a set of pre-examined macroeconomic variables such as, economic growth (GDP), risk free rates (the U.S. t-bill rates), exchange rates against USD, international oil prices and inflation in order to understand the leading factor of BRIC’s stock market returns. This paper covers the sample period from 1996:Q4 to 2013:Q1. The error correction model and Granger causality approach were applied to investigate the relationship among the variables. The results indicate that none of the explanatory variables Granger cause stock market performance in China and India. In homogenous, there is Granger causality from BRIC’s stock market performance to the risk free rates and international oil prices. This finding implies that BRIC has strong market impact or purchasing power to influence the key raw input of an economy, as well as the largest risk free investment instrument in the world. Generally, the Fed model, international trading effect and portfolio balance model are inapplicable to BRIC. The safest investment guidance for investors is to follow the changes in oil prices to forecast the movement in stock performance in Brazil. This is because there is an actual sign (from the error correction model) and significant pairwise Granger causality between stock market returns and oil prices in Brazil. Key words: stock market performance, macroeconomic variables, granger causality, risk free rates; unit root tests, cointegration tests